An interventional study on sleep hygiene among medical students - S., Cynthia Subhaprada; S., Vijayakumari; T., Rajasekhar; U., Venkateswarlu (International Journal Of Community Medicine And Public Health, 2017)
Background: Sleep deprivation, a common problem among undergraduate students, leads to daytime sleepiness and poor academic performance. The purpose of this study is to describe sleep hygiene among medical students and to measure effect of sleep hygiene educational intervention. Methods: An interventional cross-sectional study was carried out from September to October, 2015 among II MBBS students, Kurnool Medical College, Kurnool, Andhra Pradesh, India. Excessive daytime sleepiness was assessed by the Epworth sleepiness scale. Predesigned questionnaire was administered as pretest followed by health educational intervention session to 100 subjects selected by simple random sampling, and a post test two weeks later. Data entered in MS Excel 2007, was analyzed using IBM SPSS 20. Difference in means tested by paired t test and Chisquare test was used to test association between variables, with p value <0.05 considered significant. Results: 100 study subjects, 48 of 7 semester and 52 of 5 semester, had a mean (+SD) age in years, 20.2±0.58 and19.71±0.61 respectively. 57% were females. A statistically significant association between daytime sleepiness prevalence by semester was found. (Pretest X2 = 7.83, post test X2 = 7.19, p value <0.01). Weekend sleep schedules showed 2 hours increase than weekdays, in 40% (5 semester) and 30% (7 semester). 20% of study subjects had Epworth score 10-24, so expert medical advice is needed. A statistically significant difference was observed in sleep hygiene post intervention (t=2.010, p= 0.05). Conclusions: Daytime sleepiness was the most common problem encountered in this study. Sleep hygiene education promotes healthy sleeping habits.